Wear and adhesion properties of a PVD duplex coated medium alloy steel for plungers inthe oil and gas industry - Brühl, Sonia Patricia (2017)
A duplex coating consisting in plasma nitriding of V820 steel (Boehler®) and a CrAlN coating (Balinit©, Oerlikon Balzers) was designed to enhance wear properties of hydraulic fracture pumps plungers used in the O&G Industry. On subsequent reciprocating motions, pumped slurry (containing solid particles) would eventually penetrate the interstice between the plunger´s operating surface and the seal, thus causing permanent damage. The duplex system was analyzed comparing to a standard treatment for these pistons (thermal sprayed coating over carbon steel): optical and electronic microscope, depth hardness profiles, EDS and DRX. Two groups of coated samples were selected with different surface finishing, and the nitrided sample was used for comparison, so as the untreated steel. Scratch Test at different constant loads and Rockwell C indentation were used to test adhesion. Abrasion wear tests were carried out following ASTM G65. Finally, laboratory results were compared to field tests. The PVD coating were 2500 HV hard, 3-4 microns thick, and the nitrided layer provided a soft hardness depth profile of about 320 microns width. The standard thermal spray coating was 800 microns thick, with an average hardness of 750 HV but with an abrupt change in hardness with the substrate. The adhesion was extremely good, critical load was 125 N. In the abrasive tests, the mass loss in the PVD coated samples was reduced 30 times respect to the standard coated samples. In the field technological test the PVD coated pistons improved the quantity of pumping cycles in almost 300%.